Estimation of Carbon Stored in Mangrove Vegetation in Pinasungkulan Village, Minahasa Regency - Erlangga, Muhammad; Schaduw, Joshian N. W.; Paransa, Darus S. J.; Rumengan, Antonius P.; Rampengan, Royke M.; Sondak, Calvyn F. A. (JURNAL PESISIR DAN LAUT TROPIS, 2026)
Mangrove ecosystems have an important role in mitigating greenhouse gas emissions through their ability to absorb and store carbon. This study aims to determine mangrove vegetation density as well as to estimate aboveground biomass, belowground biomass, and stored carbon in Pinasungkulan Village, Tombariri District, Minahasa Regency. The method used was the line transect method with three plots measuring 10 × 10 m² on each transect and measurement of diameter at breast height (DBH) on individuals with a stem circumference ≥16 cm. The results showed four mangrove species, namely Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, and Sonneratia alba. The results of data analysis showed that tree density across 3 transects ranged from 800–1.400 ind/ha. Data analysis of aboveground biomass values across 3 transects ranged from 151,85–502,06 ton/ha with an average of 287,74 ton/ha. Data analysis of belowground biomass values across 3 transects ranged from 61,05–179,56 ton/ha with an average of 108,20 ton/ha. Data analysis of total mangrove biomass values across 3 transects ranged from 212,90–681,62 ton/ha with an average of 395,94 ton/ha. Data analysis of stored carbon values across 3 transects ranged from 100,06–320,36 ton/ha with an average of 186,09 ton/ha. Keywords: mangrove vegetation, Pinasungkulan Village, mangrove vegetation density   Abstrak Ekosistem mangrove memiliki peran penting dalam mitigasi emisi gas rumah kaca melalui kemampuan penyerapan dan penyimpanan karbon. Penelitian ini bertujuan untuk mengetahui kerapatan vegetasi mangrove serta estimasi biomassa di atas permukaan tanah, biomassa di bawah permukaan tanah, dan karbon tersimpan di Desa Pinasungkulan, Kecamatan Tombariri, Kabupaten Minahasa. Metode yang digunakan adalah metode garis transek dengan tiga plot berukuran 10 × 10 m² pada setiap transek dan pengukuran diameter batang setinggi dada (DBH) pada individu dengan keliling batang ≥16 cm. Hasil penelitian menunjukkan empat spesies mangrove, yaitu Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, dan Sonneratia alba. Hasil analisis data  kerapatan pohon pada 3 transek berkisar antara 800–1.400 ind/ha. Analisis data nilai biomassa di atas permukaan tanah pada 3 transek berada pada kisaran 151,85–502,06 ton/ha dengan rata-rata 287,74 ton/ha. Analisis data nilai biomassa di bawah permukaan tanah pada 3 transek berkisar 61,05–179,56 ton/ha dengan rata-rata 108,20 ton/ha. Analisis data nilai biomassa total biomassa pada 3 transek berada pada kisaran 212,90–681,62 ton/ha dengan rata-rata 395,94 ton/ha. Analisis data nilai karbon tersimpan pada 3 transek berkisar antara 100,06–320,36 ton/ha dengan rata-rata 186,09 ton/ha. Kata kunci: vegetasi mangrove, Desa Pinasungkulan, kerapatan vegetasi mangrove